Apolipoprotein C3 C1100T and C3238G Polymorphisms and Cardiovascular Disease Risk among Obese Type 2 Diabetics in Southwestern Nigeria (African Journal of Biomedical Research, 2024)
Obesity is associated with cardiovascular disease (CVD) risk and type 2 diabetes mellitus (T2DM). Apolipoprotein (APO) C3 C3238G and C1100T gene polymorphisms are risk factors for CVD but their relationship with obesity and T2DM in Black Africans has not been fully elucidated. Association of these gene polymorphisms with hypertension and dyslipidemia among obese type 2 diabetics in a Southwest Nigerian population was assessed.One hundred and thirty-eight (138) non-obese diabetics, 107 obese diabetics, 100 obese non-diabetics and 100 control subjects attending metabolic clinic in Osun State Nigeria were enrolled. Anthropometric parameters were measured. Fasting blood sugar (FBS), lipid profile and APOC3 protein were estimated   using standard lab procedures. APOC3 gene polymorphisms were analyzed by polymerase chain reaction - restriction fragment length polymorphism. Data were analyzed   and significant level set at p